Analysis of determinants of manufacturing company value - Ardiani Ika Sulistyawati; Yulianti Yulianti; Rosyati Rosyati; Dian Triyani (Institute of Computer Science (IOCS), 2023)
In general, the company's goal is to maximize company value as reflected in the share price and increase the wealth of company owners by achieving targeted profits. This research aims to analyze the influence of dividend policy, investment decisions, liquidity, profitability, capital structure and company size on company value. The objects of this research are all manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2021 period. This research uses secondary data obtained through documentation methods. The results of this research prove that investment decisions, profitability, capital structure and company size have a significant effect on company value. Meanwhile, dividend and liquidity policies have no influence on company value. The resulting coefficient of determination was 84.9%.